Portfolio Concentration and the Performance of Individual Investors - Ivković, Zoran; Sialm, Clemens; Weisbenner, Scott (Journal of Financial and Quantitative Analysis, 2008)
Abstract This paper tests whether information advantages help explain why some individual investors concentrate their stock portfolios in a few stocks. Stock investments made by households that choose to concentrate their brokerage accounts in a few stocks outperform those made by households with more diversified accounts (especially among those with large portfolios). Excess returns of concentrated relative to diversified portfolios are stronger for stocks not included in the S&P 500 index and local stocks, potentially reflecting concentracted investors' successful exploitation of information asymmetries. Controlling for households' average investment abilities, their trades and holdings perform better when their portfolios include fewer stocks.